PEMBANGKIT LISTRIK TENAGA SURYA OFF GRID DAN APPLIKASINYA - Utomo, Darmawan; Handoko, Handoko; Murtianta, Budihardja (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
As a tropical country and elongated on the equator, Indonesia greatly benefits from high exposure to sunlight irradiation. This energy can be harvested and used as a substitute for fossil energy which produces a lot of pollution. Unfortunately, this technology is not yet known to many people, including STEM teachers, how to implement it. Schools have a double advantage if they use solar energy because they have a large area and are active when there is exposure to sunlight. This article describes training activities for five MIPA teachers at SMA Kristen I Salatiga. This is a form of disseminating the knowledge possessed by the SWCU Electronics and Computer Engineering Faculty instructors. From the average questionnaire result of 4.76, it can be concluded that they got new knowledge and also stated that solar energy mining is actually quite easy to implement in schools.